The Constituent Elements of the Labor Potential Team Составные элементы трудового потенциала коллектива - Golubev Stanislav N. (Bìznes Inform, 2012)
The article specifies the nature of the concept of "employment potential" and its components are defined at different levels of study. It is concluded that the employment potential of each of the higher levels is complemented by an additional element that characterizes the benefits of interaction. But there is another factor characterizing the cost of interaction and group work. Thus, in some cases, it is more than the benefits of the association. Therefore, it is a group or organizational capacity has the largest reserves of the development and use. В статье уточнена сущность понятия «трудовой потенциал» и определены его составляющие на разных уровнях исследования. Сделан вывод о том, что трудовой потенциал на каждом из высших уровней дополняется дополнительным элементом, характеризующим выгоды от взаимодействия. Но существует и другой фактор, характеризующий затраты на взаимодействие и групповую работу. При этом в некоторых случаях он бывает больше, чем выгоды от объединения. Поэтому именно групповой, или организационный потенциал имеет наибольшие резервы развития и использования.